(untitled) (International Conference on Multidisciplinary Sciences and Educational Practices, 2025)
This article examines the formation of the judicial corps in the Republic of Uzbekistan, in particular, the procedure for appointing judges and their current state, the relevance of their improvement, and proposals for the formation of the judicial corps and improving the procedure for appointing judges, studying the experience of Japan in appointing judges, and their importance.